Focusing basic research for cassava varietal improvement - Iglesias F., Carlos Ariel; Bonierbale, Merideth W.; El-Sharkawy, Mabrouk A.; Lozano T., José Carlos; Bellotti, Anthony C.; Wheatley, Christopher C. (International Center for Tropical Agriculture, 1995)
Cassava is an important energy-rich food for millions of people in tropical developing countries. The crop has reached that status after thousands of years of evolution under diverse agro-ecosystems, movement of germplasm within and across continents, and more recently, through scientific genetic enhancement. Understanding that process will help in focusing the strategy for the development of basic research toward varietal improvement. This review analyzes the potential of genetic improvement as a tool for socio-economic constraints and challenges in cassava production and utilization. An analysis on cassava genetic resources, the assembly, maintenance and characterization of existing genetic diversity is presented. It also refers to methodologies for the creation of new genetic diversity, and multi-institutional approach to gene-pool development in cassava. Finally, some of the major challenges and opportunities in basic research to sustain cassava genetic improvement are discussed and a continued and increased emphasis on broad-based breeding programs for cassava in developing countries, combined with the use of biotechnology when appropriate is advocated